Bachelor Degree in Medicine and Surgery Community Medical Training Curriculum Contribution on Equity and Quality of Health Care in Namibia - Lukolo, Linda N.; Sheehama, J.; Munyika, A. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2018)
Community involving a population-focused, organized effort to help individuals, groups and communities reduce health risks, and maintain or improve health status”. The Community Medicine departments of medical colleges should be more involved in integrated teaching with clinical disciplines and should also be involved in the delivery of services in the teaching hospital and in primary health care settings, such as in immunization, guidance/counselling, biomedical waste management and infection control. All stakeholders in University education recognize its invaluable contribution to the quality of university training. “Field Attachment” to mean any approved field-based practical work carried out by staff and students for the purpose of teaching and / or research in places outside the University control. The objective of community medicine based training at the University is to produce practically oriented graduates that meet the required medical profession related competences of the community of their future service. Through community medicine attachment, medical students are enabled to associate themselves with the health and medical needs of the communities, this association will enable the students feel their own gap on these health issues to address them, or to be able to manage them.